Thallium-based HTS thin films, processing, properties and applications - Bramley, A; O'Connor, J; Grovenor, C (IOP, 1999)
Thin films of the Tl-based high-temperature superconducting (HTS) phases are beginning to find application in a number of practical devices, especially in the field of microwave communication systems. This review describes the issues surrounding the fabrication of thin films of the thallium-based HTS materials. The influence of thermodynamics and kinetics, the various potential thalliation techniques and the selection of an appropriate substrate material are all important considerations when designing a process for the fabrication of thin films of these highly reactive materials. The properties of the resulting films are critically dependent on the microstructures developed during thalliation. Microstructural evolution during thalliation, the effect of structural defects on the properties of such films and the importance of achieving biaxial grain alignment in optimizing the properties of the films are all discussed.